2021
DOI: 10.1186/s12891-021-04888-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical efficacy of a femoral neck system versus cannulated screws in the treatment of femoral neck fracture in young adults

Abstract: Background To compare the clinical efficacy of a femoral neck system (FNS) and cannulated screws (CS) in the treatment of femoral neck fracture in young adults. Methods Data from 69 young adults, who were admitted for femoral neck fracture between March 2018 and June 2020, were retrospectively analyzed. Patients were divided into two groups according to surgical method: FNS and CS. The number of intraoperative fluoroscopies, operative duration, len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 24 publications
6
45
0
Order By: Relevance
“…Non-displaced fractures in high-risk patients with multiple comorbidities also represent well-accepted indications for fixation. Since its introduction in 2018, the FNS has expanded the spectrum of available fixation systems [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 22 , 24 ]. It is assumed to be less invasive, thereby potentially reducing perioperative risks [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Non-displaced fractures in high-risk patients with multiple comorbidities also represent well-accepted indications for fixation. Since its introduction in 2018, the FNS has expanded the spectrum of available fixation systems [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 22 , 24 ]. It is assumed to be less invasive, thereby potentially reducing perioperative risks [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies compared the FNS with three cannulated screws [ 14 , 15 , 16 , 18 ] and observed heterogeneous outcomes. He et al reported shorter but not significantly different ORT, less radiation, a lower complication rate, and no differences in LOS [ 14 ]. Tang et al confirmed the reduced fluoroscopy time in the FNS group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With increasing age, the hip joint undergoes gradual wear, which, combined with the decreasing fracture resistance capacity of the elderly, leads to high incidence of hip fracture [ 1 – 3 ]. According to a World Health Organization survey report, 30.0% of hip fractures worldwide occur in China [ 4 ], and surgery is the preferred treatment modality for patients without surgical contraindications, but 32.3% of patients will experience perioperative complications, with a probability of dying from complications reaching 30.0% 1 year after surgery and risk of death lasting for up to 10 years [ 5 – 7 ]. Among all the causes of postoperative death in patients with hip fracture, cerebrovascular accidents take the first place, so it is extremely important to explore the risk factors that induce cerebrovascular accidents.…”
Section: Introductionmentioning
confidence: 99%